Pengenalan Bisnis Digital Bagi Generasi Muda Dalam Menumbuhkan Jiwa Kewirausahaan Pada Siswa SMKN 3 Kabupaten Seluma - Irwanto, Tito; Abi, Yudi Irawan; Herlina, Yeni; Melinda, Tri Febrina; Ariantara, Yudi (Universitas Dehasen Bengkulu, 2025)
Introducing understanding and education to teachers and students of SMKN 3 Seluma begins by explaining the material about the Introduction of Digital Business for the Young Generation in Fostering the Spirit of Entrepreneurship in Students by downloading the Profit Anywhere application, this activity is also a forum for lecturers of the Faculty of Economics, Dehasen University to implement learning or theories that have been taught in lectures because in the world of work to come, students are required to be smart in choosing the type of entrepreneurship or can choose to become entrepreneurs who can create their own jobs instead of relying on jobs that are open to the public and many competitors. In this activity, students are also given an understanding of how to become a young entrepreneur who can provide benefits to many people.